Prevalensi Koksidiosis dan Identifikasi Eimeria sp. Pada Kelinci Berbagai Umur di Kecamatan Kalibagor Kabupaten Banyumas - Pramudya, Ruzicca Arif; Sufiriyanto, Sufiriyanto; Indrasanti, Diana (ANGON: Journal of Animal Science and Technology, 2020)
Background. The purpose of this study are to determine the prevalence of coccidiosis, to know the species of Eimeria, and to find out the difference in the prevalence of coccidiosis in various age rabbits in Kalibagor Subdistrict Banyumas Regency. Materials and methods. The targets of this study is various types of rabbits in Kalibagor Subdistrict Banyumas Regency at three periods, namely weaning (1-5 weeks), growing (6-24 weeks), and adult (>24 weeks) with a minimum 3 rabbit of each farmer. The method used was a survey method using purposive sampling. Data analysis was performed using descriptive and chi square methods. The samples used for this study were rabbit's faeces as much as 5 grams per animal in the weaning period as many as 31 , 31 growing, and 31 adult. Result. The results of the analysis show that the species of Eimeria identified as infecting rabbits includes Eimeria magna, Eimeria perforans, Eimeria flavescens, Eimeria intestinalis, Eimeria exigua, Eimeria media, Eimeria coecicola, and Eimeria stiedae. The prevalence of coccidiosis in rabbits weaning period was 29,03%, the growing was 31,18%, and the adult was 29,03% and the total prevalence of coccidiosis were 89,24%. P>0,05 shows that there are no difference in the prevalence of coccidiosis in rabbits of various ages in Kalibagor Subdistrict Banyumas Regency. Conclusion. The conlusion of this study is that the prevalence of coccidiosis was noy significantly different in rabbits in weaning, growing, and adult period.